Preliminary analysis of the metabolic and physical activity profiles of mice lacking the slc43a3-encoded equilibrative nucleobase transporter 1 - Aaron L. Sayler; James R. Hammond (PLoS ONE, 2025)
SLC43A3 encodes for a membrane transporter selective for purine nucleobases (equilibrative nucleoside transporter 1; ENBT1). Adenine, an endogenous substrate for ENBT1, plays an important role in many biochemical and physiological processes, including cellular energy metabolism. To investigate how the loss of ENBT1 impacts these processes, we generated a slc43a3-null (global; KO) mouse model. Metabolic function, physical activity, and food and water consumption were assessed in male and female wild-type (WT) and KO mice (age 10–12 weeks) for a 60-hour period (12 hr light/dark cycle). Blood pressure and heart rate of each group of mice were also assessed using a rodent tail cuff method. Male KO mice showed a significant increase in metabolic activity relative to male WT mice. Male KO mice also displayed a significant decrease in rearing activity and blood pressure. Female KO mice did not show the same changes in metabolic and physical activity as the males, but did display a significant 4-hour negative change in diurnal rhythm phase in the metabolic and activity measures that was not seen for the male KO mice. It may be concluded that loss of slc43a3-encoded ENBT1 impacts numerous measures of activity in mice, with female mice impacted differently than male mice. This may reflect disruption of purinergic processes associated with energy metabolism coincident with changes in cellular adenine availability.